LA PARTICIPACION DE LA BASE SOCIAL EN LAS COOPERATIVAS RURALES: TRES CASOS EN CUNDINAMARCA 1992 - Correal, Catherine M. (2012)
LA PARTICIPACION DE LA BASE SOCIAL EN LAS COOPERATIVAS RURALES: TRES CASOS EN CUNDINAMARCA 1992